Kinetic profile and catalytic activity of transition metal-based ionic liquids for reduction of nitroarenes via in situ formation of nanoparticles - Thawarkar, Sachin R.; Khupse, Nageshwar D.; Kumar, Anil (Chemistryselect, 2017)
The experimentally determined apparent rate constant (k(app)) shows that the [BmIm](2)[PdCl4] and [BmIm](2)[NiCl4] act as effective catalysts for the reduction of nitroarenes to aminoarenes in the presence of NaBH4. The TEM, XPS, XRD and dynamic light scattering studies show that there is in situ formation of Pd and Ni metal Nanoparticles (NPs) from the reduction of [BmIm](2)[PdCl4] and [BmIm](2)[NiCl4], respectively which are responsible for the enhancement in the catalytic activity. Thus, in the presence of the ionic liquid stabilized metal NPs show higher catalytic activity in comparison to the NPs stabilized with other capping agents as reported. The order of k(app) as 1) PNP > 2-BrPNP > 2-APNP and 2) PNP > ONP > 2-NR for reduction of nitroarenes using [BmIm](2)[PdCl4] and [BmIm](2)[NiCl4] and its correlation explained on the basis of electronic structure and hydrogen bonding ability of nitroarenes. The thermodynamic parameters such as E-a, Delta H-#, Delta S-# and Delta G(#) are in agreement with the surface catalyzed reduction reaction of PNP in the presence of NPs as catalyst. The kapp values illustrated the reduction reaction follow the LangmuirHinshelwood (L-H) mechanism.